TNF-α-Mediated Endothelial Cell Apoptosis Is Rescued by Hydrogen Sulfide - Lorena Diaz Sanchez; Lissette Sanchez-Aranguren; Keqing Wang; Corinne M. Spickett; Helen R. Griffiths; Irundika H. K. Dias (MDPI AG, 2023)
Endothelial dysfunction is implicated in the development and aggravation of cardiovascular complications. Among the endothelium-released vasoactive factors, hydrogen sulfide (H2S) has been investigated for its beneficial effects on the vasculature through anti-inflammatory and redox-modulating regulatory mechanisms. Reduced H2S bioavailability is reported in chronic diseases such as cardiovascular disease, diabetes, atherosclerosis and preeclampsia, suggesting the value of investigating mechanisms, by which H2S acts as a vasoprotective gasotransmitter. We explored whether the protective effects of H2S were linked to the mitochondrial health of endothelial cells and the mechanisms by which H2S rescues apoptosis. Here, we demonstrate that endothelial dysfunction induced by TNF-α increased endothelial oxidative stress and induced apoptosis via mitochondrial cytochrome c release and caspase activation over 24 h. TNF-α also affected mitochondrial morphology and altered the mitochondrial network. Post-treatment with the slow-releasing H2S donor, GYY4137, alleviated oxidising redox state, decreased pro-caspase 3 activity, and prevented endothelial apoptosis caused by TNF-α alone. In addition, exogenous GYY4137 enhanced S-sulfhydration of pro-caspase 3 and improved mitochondrial health in TNF-α exposed cells. These data provide new insights into molecular mechanisms for cytoprotective effects of H2S via the mitochondrial-driven pathway.